Covid-19 excess mortality in Paraiba and the most affected counties - Ferreira, Assel Muratovna Shigayeva (2022)
The impact of COVID-19 pandemic in terms of number of deaths varied widely across the territories of Brazil with a significant number of deaths underreported. In this sense, the mortality statistics investigation focusing on subsequent analysis that triggering specific chain of events, could draw attention to the reliability of mortality information, scope, and severity of exceed deaths and real impact of pandemic. The present study aimed to analyze the magnitude and temporal course of excess mortality associated with the COVID-19 pandemic in 2020 in Paraiba state and its most affected municipalities. The following methodological steps were performed: comparative analysis of quality of the Brazilian mortality data sources; investigation of the quality of mortality statistics: analysis of the coverage by General Growth Balance method application, analysis of deaths registration completeness by redistribution of ill-defined causes and redistribution of garbage codes; and excess deaths estimation for 2020 in Paraiba based on weekly 2015-2019 time-series. The results of the study evidenced contradicted information released by five official Brazilian mortality data sources not only in terms of volume of COVID-19 deaths, but in interpretation of specific events such as time lag, pandemic picks, and weekly distribution of deaths. The data quality correction after coverage and completeness analysis showed significant increasing of deaths volume in Paraiba and its municipalities for 2020. The study showed clear evidence of statistically significant excess mortality due all-causes, natural causes and respiratory diseases in Paraiba 2020 with disclosure of direct and indirect impact of pandemic, specific demographic characteristics and weekly distribution of deaths. Due to the gaps in a scientific knowledge about excess mortality and the quality of mortality statistics under unprecedented circumstances in Paraiba during pandemic 2020, this study could benefit towards improvement of vital statistics in the state and contribute to better understanding of real pandemic impact to future policy making.